(untitled) (City: History, Culture, Society, 2023)
The purpose of this study is to locate on the territory of modern Kyiv’s Podil the XVII–XVIII-century buildings that no longer exist but were depicted on city plans of the late XVII – early XIX centuries, mentioned in written sources, and studied archaeologically in the XIX–XX centuries. The novelty of the research lies in the demonstration, using Kiev as an example, of the possibility of topographic reconstructions of certain areas of construction in contemporary Ukrainian cities, based on the integrated use of various categories of historical sources. Research methodology consists of scientific principles, historicism, objectivity, analysis methods, classification, generalization, historical-genetic, and historical-typological approaches. The primary outcomes of the study are the localization of three wooden temples (destroyed by fire in 1811), two monastic courtyards (whose owners changed after the secularization of church estates in 1786), and one private estate on the territory of modern Kyiv’s Podil, which changed its function during the seventeenth and eighteenth centuries. Prospects for future research include expanding knowledge of the historical development of Kiev’s Podil during the seventeenth and eighteenth centuries through the discovery of new historical sources, with the help of which it will be possible to locate additional buildings in this urban historical district. The practical significance of the achieved results is that they can be used to write scientific researches, popular science articles and tour guides, create museum exhibits, etc. The originality of the study lies in the fact that for the first time using a complex of historical sources on the modern topographic basis of Kyiv’s Podil, the Church of the Savior, Church of the Holy Spirit, and Church of St. Basil, as well as Mezhyhirya’s and Pereyaslav’s monastic courtyards and Tornoviot’s estate – silk garden – old contract house are localized.